Rumors of restoration: Joe Biden's foreign policy and what it means for Canada. Issue 2 (4th May 2021) - Ettinger, Aaron
ABSTRACT: The election of Joe Biden in the 2020 presidential elections suggests a return to "normal" foreign relations after the dramatic four years of Donald Trump's presidency. This paper asks two questions: what will Biden's foreign policy look like? And what are its implications for Canada. Fundamentally, Biden aims to restore the status quo ante Trump in US foreign policy while also adjusting to a world has irreversibly changed. This paper outlines the parameters of Biden's nascent foreign policy using a seven-point framework focusing on worldview, (2) problem definition, (3) approach to international order; (4) security; (5) economics; (6) values; and (7) personality and decision-making process. For Canada, Biden's election relieves the immediate upheavals of Donald Trump's presidency, but it does not necessarily clarify Canada's foreign policy outlook. Canada still must establish its relative priorities between the continent that is the foundation of its prosperity and security, and the internationalism that is the vehicle of Canada's international identity and influence.